The Modulatory Activity of Tryptophan Displaying Nanodevices on Macrophage Activation for Preventing Acute Lung Injury - Sun, Liya; Wang, Rui; Wu, Chenchen; Gong, Jiameng; Ma, Huiqiang; Fung, Shan-Yu; Yang, Hong (Frontiers in Immunology, 2021)
Macrophages play an important role in the initiation, maintenance and resolution of inflammation in many human diseases. Effective regulation of their activation and immune responses could be a promising therapeutic strategy to manage various inflammatory conditions. Nanodevices that naturally target macrophages are ideal agents to regulate immune responses of macrophages. Here we described a special tryptophan (Trp)-containing hexapeptide-coated gold nanoparticle hybrids, PW, which had unique immunomodulatory activities on macrophages. The Trp residues enabled PW higher affinity to cell membrane, and contributed to inducing mild pro-inflammatory responses of NF-kB/AP-1 activation. However, in the presence of TLR stimuli, PW exhibited potent anti-inflammatory activities through inhibiting multiple TLR signaling pathways. Mechanically, PW was internalized primarily through micropinocytosis pathway into macrophages and attenuated the endosomal acidification process, and hence preferentially affected the endosomal TLR signaling. Interestingly, PW could induce the expression of the TLR negative regulator IRAK-M, which may also contribute to the observed TLR inhibitory activities. In two acute lung injury (ALI) mouse models, PW could effectively ameliorate lung inflammation and protect lung from injuries. This work demonstrated that nanodevices with thoughtful design could serve as novel immunomodulatory agents to manage the dysregulated inflammatory responses for treating many chronic and acute inflammatory conditions, such as ALI/ARDS.